STRATEGI KOMUNIKASI INTERPERSONAL CHIEF EXECUTIVE OFFICER LILY PROJECT JEMBER DALAM MENINGKATKAN MOTIVASI KERJA TIM - Arif Fidiatus Soliha (Universitas Muhammadiyah Jember, 2023)
Team motivation is the most important key in a company. This cannot be separated from how a leader prepares a strategy and the efforts made to create a new atmosphere that raises the motivation of the team to provide the best results in their performance. One of the strategies that underlies all aspects that can be carried out is communication. This then became the reason researchers were interested in taking up research with the title Lily Project Jember Chief Executive Officer's Interpersonal Communication Strategy in Increasing Teamwork Motivation. This research is useful as material for consideration in behavior in the work environment so that all involved can function optimally and effectively. This research is descriptive qualitative research taking objects from companies operating in the Lily Project Jember service sector. The data collection methods applied involve observation, interviews and documentation. The data obtained is then processed through the stages of data reduction, data presentation, and drawing conclusions. In this research, the results obtained can be explained that the interpersonal communication strategy owned by the company and applied by a leader to the team under him is very effective in increasing team work motivation, where this motivation not only has a positive impact on the company but also has a positive impact on everyday life. -every individual's day, although in the communication process there are several obstacles found both from the leader and each individual. Keywords: Interpersonal Communication; Chief executive officer; Teamwork Motivation